Compressor Valve Maintenance on CC 205 UPT Locomotive Depot Divre IV Tanjung Karang - Fajar Paundra; Rene hario galih; Fuad Mulkan Al Machzumy; Alan Maulana Yusuf; Kevin Saputra; Anugrah Nan Agung; Puguh Elmiawan (Department of Industrial Engineering, Universitas Jenderal Soedirman., 2023)
The CC 205 locomotive at the UPT Locomotive Depot Divre IV Tanjung Karang is a train that uses diesel fuel. The locomotive at UPT Locomotive Depot Divre IV Tanjung Karang experienced compressor damage, which required component replacement. This research aims to identify and carry out the process of treating valve leaks in locomotive compressors. Observation, interview, and documentation are used to obtain appropriate data and results. Maintenance carried out on this locomotive is necessary so that the CC 205 locomotive can be used optimally without any doubt. Maintenance is an activity in maintaining existing facilities by carrying out repairs or replacements necessary to maintain the condition of these components so that they are always in maximum condition. The analysis results show that air leaks in the compressor caused by compressor valve leaks can cause the pressure in the main tank not to be filled.